PROBLEMS FACED BY ELEMENTARY SCHOOL TEACHERS IN CURRICULUM 2013 IMPLEMENTATION - Watana, Selvia Amia; Utaya, Sugeng; Djatmika, Ery Tri (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
Pasar Lama Elementary School 1 Banjarmasin have practiced Curriculum 2013 in academic year 2014/2015. In the implementation of this new Curriculum, the teachers face problems. Therefore, this research analyzes the problem and solution in the Curriculum implementation. This research aims to find the problem and solution of Curriculum implementation. The research used description method. The population were teachers at Pasar Lama Elementary School 1 Banjarmasin with 26 teachers as sample and data collected through questioners and documentation with descriptive analysis. The problem percentage was 58.48% (high category). The problems include syllabus, Lesson Plan, assessment, and remedial. The solution used was teacher working and supervision.